Evaluation of Vocational School (SMK) Students’ Environmental Literacy - Maknun, Johar; S. Barliana, M.; Cahyani, Diah; Dalil H., Nanang; Dahar Minghat, Asnul (International Journal of Engineering and Technology, 2018)
This research evaluates the level of environmental literacy of vocational students. The research method used is evaluative descriptive research method. The instrument used is the Environmental Literacy Test. The component of environmental literacy consists of environmental knowledge, attitudes, and "actions" or responsible behavior for the environment. Mastery of the environmental concept of vocational students is based on the achievement of environmental literacy in terms of knowledge and environmental understanding which consists of 8 indicators, i.e.: energy, pollution and contamination, forests, atmosphere / climate, water, waste, and sustainable development. The average mastery of environmental concepts is 51, which included to the low category. The highest knowledge and understanding are population indicators that is an average value of 68 and the lowest value is an atmospheric / climate indicator with an average value of 32. Attitudes and participation in overcoming environmental problems are included in the good category. They have tried to use alternative transportation such as by using bicycle or walking, reducing the use of electricity for lighting and cooling the space, using water as needed, and disposing the garbage in the proper place. Vocational students are still lacking in action as an effort to overcome environmental problems.Â Â